Best Practices in Promoting Students’ Reading Habit in Extensive Reading Class - Vivit Rosmayanti; Muhammad Yahrif (STAI Hubbulwathan Duri, 2023)
A literate culture must be created for this world, and reading habits are crucial. It moulds a person's personality and aids in their ability to think clearly and come up with original ideas. This study aimed to highlight best practices in promoting students’ reading habits in extensive reading classes. This study employed a qualitative grounded research design. The participants of the study were students of the English department at one of private university in Makassar. The data were collected by conducting semi-structured interviews and classroom observation. The interview transcript and the field notes from the observation were analyzed using a grounded research approach. There are three steps of codification of the grounded research approach: open coding, axial coding, and selective coding. The result of this study revealed seven successful activities applied in supervised (instructed) Extensive Reading classes; some are everyday reading activities, some are modified reading activities, and the lecturer creates others to promote students' reading habits. They were: 1) Jigsaw reading, 2) Jumbled reading, 3) Paraphrasing reading quiz, 4) Reconstructing reading story, and 5) Vocabulary reading challenge. 6) Book response form presentation, and 7). Survey reading. It can be concluded that the student's responses are very positive since they encourage them to read at home or anywhere, not only in class. It is recommended for the teachers should work in collaboration to develop interest of students in reading materials through digital media.